Pengembangan Bahan Ajar Introduction to Linguistics Berbasis Pendekatan Komunikatif Pada Mahasiswa Jurusan Bahasa Inggris FBS UNM - Abdullah, Abdullah; Jabu, Baso; Haryanto, Haryanto; Sakkir, Geminastiti (Seminar Nasional LP2M UNM, 2025)
Abstrak. The problem of this research is how to develop learning material of Introduction to Linguistics based on communicative approach for English Department students of FBS UNM, the factors that influence the implementation of materials design, worksheets exercises and lecture program which are expected to improve students' knowledge and language skills. This research is a development research that aims to develop Introduction to Linguistics learning material design based on communicative approach for students of the English Department of FBS UNM to improve students' knowledge and language skills. Developing learning material design that is planned will follow the research and development designed by Borg & Gall (1983). This research is an extensive process in assessing students' needs and then specially designed products are developed to improve their language knowledge and skills through a communicative approach based on Introduction to Linguistics learning. The population of this research was the students of English Department of FBS UNM. The research sample was the students of the English literature study program. The result of the research shows that, there is a form of Introduction to Linguistics prototype teaching materials, syllabus, and lecture contracts as well as communicative approach based on Linguistics learning quide book.Kata kunci: Developing Learning, Linguistics, Communicative Approach.